2008
DOI: 10.1111/j.1469-0691.2008.02096.x
|View full text |Cite
|
Sign up to set email alerts
|

Weak effect of metal type and ica genes on staphylococcal infection of titanium and stainless steel implants

Abstract: Currently, ica is considered to be the major operon responsible for staphylococcal biofilm. The effect of biofilm on susceptibility to staphylococcal infection of different implant materials in vivo is unclear. The interaction of ica-positive (wild-type (WT)) and ica-negative (ica(-)) Staphylococcus aureus and Staphylococcus epidermidis strains with titanium and both smooth and rough stainless steel surfaces was studied by scanning electron microscopy in vitro and in a mouse tissue cage model during 2 weeks fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 46 publications
0
33
0
Order By: Relevance
“…Therefore, we selected compound 1 to study deposition on implant materials. Rough and smooth titanium (19), as well as steel, which are both utilized in implants, were used as substrates for the deposition of compound 1. In addition, compound 1 was deposited on oriented gold monolayer Au(III) on glass as a smoother model surface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we selected compound 1 to study deposition on implant materials. Rough and smooth titanium (19), as well as steel, which are both utilized in implants, were used as substrates for the deposition of compound 1. In addition, compound 1 was deposited on oriented gold monolayer Au(III) on glass as a smoother model surface.…”
Section: Resultsmentioning
confidence: 99%
“…epidermidis biofilm-associated infection has been studied using multiple models, most frequently by subcutaneous inser- (19). The bacteria consist of a floating population in the tissue cage fluid and an adherent population in the biofilm, the former being fed by the turnover of the latter.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies show that increasing surface roughness can increase bacterial adhesion, with polished TAN surfaces displaying lower adhesion than standard microrough TAN [6]. Hudetz et al have shown that titanium offers at most a minor improvement in infection risk in an in vivo model, although the subcutaneous implant does not bear close consideration for fracture care implants [22]. Few clinical studies have compared titanium and EPSS implants in humans.…”
Section: Discussionmentioning
confidence: 99%
“…S. aureus is known to secrete a number of surfaceassociated proteins that are potent stimulators of bone resorption [4]. S. aureus is also capable of producing a protective exopolysaccharide biofilm which plays a major role in infection especially with respect to treatment, even though its role in the development of infection is weak [5]. The use of local antibiotic delivery systems, especially antibiotic-loaded bone cement, is a well established procedure in the treatment of musculoskeletal infections [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%